Dental pulp stem cells conditioned medium-functionalized microspheres for endodontic regeneration - Gao, Jing; Wang, Yuhan; Zhang, Tongxing; Qu, Jiafei; Liu, Qian; Chen, Yao; Xu, Baoshan; Shen, Jing (Frontiers in Cell and Developmental Biology, 2025)
IntroductionDental pulp disease represents a prevalent oral pathology with limited success in functional regeneration of the pulp-dentin complex. Stem cell-based endodontic regenerative therapy has emerged as a promising approach, leveraging the principles of tissue engineering through the combination of stem cells, scaffolds, and growth factors. However, recreating the native pulp microenvironment remains a critical challenge.MethodsThis study developed a novel strategy to mimic the dental pulp regeneration microenvironment using nucleus pulposus microspheres (NPM) loaded with conditioned medium (CM) for dental pulp stem cells (DPSCs). The biocompatibility of NPM and the effects of NPM-loaded CM on DPSCs differentiation and angiogenesis were systematically evaluated. A semi-isotopic in vivo model was employed to assess pulp-like tissue regeneration.ResultsNPM exhibits good biocompatibility, and NPM-loaded CM enhances the odontogenic differentiation and angiogenic potential of DPSCs. Furthermore, the DPSCs+ NPM + CM complexes promoted the regeneration of pulp-like tissue in an in vivo semi-isotopic model. Mechanistically, key bioactive cues secreted in the CM mediated the multi-directional differentiation potential of DPSCs, thereby facilitating pulp tissue regeneration.DiscussionThe 3D pulp-specific microenvironment, facilitated by NPM and CM bioactive factors, enables the regeneration of the pulp-dentin complex, offering a novel strategy and experimental basis for pulp regeneration.